2017
DOI: 10.3928/01477447-20170608-01
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Opioid Use After Total Shoulder Arthroplasty With Injectable Liposomal Bupivacaine Versus Interscalene Block

Abstract: Postoperative pain control is a significant concern after total shoulder arthroplasty. Injectable periarticular liposomal bupivacaine, which has been found to decrease opioid use after orthopedic procedures, has been proposed as a viable alternative to regional anesthesia. This study compared the efficacy of liposomal bupivacaine vs interscalene block among patients undergoing total shoulder arthroplasty. A retrospective review was conducted of 79 patients who underwent anatomic total shoulder arthroplasty per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . We identified four RCTs 20 , 25 , 27 , 28 and three retrospective controlled studies 18 , 19 , 26 in our study. The trials compared LB vs INB for pain control after TSA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the included studies are summarized in Table 1 . We identified four RCTs 20 , 25 , 27 , 28 and three retrospective controlled studies 18 , 19 , 26 in our study. The trials compared LB vs INB for pain control after TSA.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of pain score at 12 hours after TSA were reported in five studies. 19 , 20 , 26 – 28 Given the significant heterogeneity among these studies ( I 2 =53%, P =0.07), a random- effects model was used. The pooled results revealed that the two groups had comparable pain scores at 12 hours (SMD =−0.01, 95% CI=−0.33 to 0.31, P =0.96; Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations